Pemberdayaan Ibu PKK dalam Pembuatan Produk Pewangi Pakaian Spray Menggunakan Aromaterapi Bunga Lavender di Desa Paddingin, Kec. Sanrobone. Kab. Takalar - Tahir, Masdiana Tahir; Sukmawati Sukmawati; Zainal Abidin (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2026)
Fabric fragrance is a household product commonly used during the laundry process to provide a pleasant and long-lasting scent to clothes and to prevent musty odors during storage. However, fragrances added during the final washing stage are often less effective because their scent decreases after the drying process. Therefore, an innovation in the form of a lavender aromatherapy fabric fragrance spray was developed. This spray is applied to clothes after drying and can also be used during folding or ironing. Lavender aromatherapy offers several benefits, including relaxation effects, sedative properties, anxiety reduction, and mood improvement. In addition, lavender flowers act as a natural insect repellent because they are effective in controlling mosquitoes. Considering these benefits, a community empowerment program was conducted for non-productive women in Paddingin Village who are members of the Family Welfare Movement (PKK) organization. The purpose of this community service program was to provide training on the preparation of lavender aromatherapy fabric fragrance spray for PKK women in Paddingin Village, Sanrobone District, Takalar Regency, one of the assisted villages of LPkM UMI. The training included an introduction to the benefits of lavender, the preparation process of the spray product, and practical demonstrations. Through this activity, PKK women are expected to independently produce lavender aromatherapy fabric fragrance spray at home for household use and as a potential small-scale business opportunity to support family income.